Preparation method and application of modified NCM positive electrode material
By using pentafluorophenylpropyltrimethoxysilane (PFPPS) on the surface of high-nickel ternary cathode material to form a self-assembled molecular layer, the stability and electrochemical performance problems of the material when stored in air are solved, and significant storage stability and electrochemical performance improvements are achieved.
Patent Information
- Application Number
- CN202411820643.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
AI Technical Summary
When stored in the air, high-nickel ternary cathode materials are susceptible to moisture, resulting in the loss of active lithium and the damage to the crystal structure, and are prone to form impurity layers to hinder the diffusion of lithium ions, reducing the rate performance and cycle stability of the material.
Pentafluorophenylpropyltrimethoxysilane (PFPPS) is used as the surface modifier to form a multifunctional molecular layer by self-assembly on the surface of the NCM positive electrode material, removing the residual lithium on the surface, forming a protective layer and establishing a hydrophobic barrier.
It significantly improves the air storage stability and electrochemical performance of NCM positive electrode materials, effectively inhibits the dissolution of transition metal ions, improves lithium ion transport, and enhances structural stability.
Smart Images

Figure CN119725435A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of lithium ion batteries, and in particular to a preparation method of a modified NCM positive electrode material and application thereof. Background Art
[0002] As the world pays more and more attention to sustainable development and clean energy, lithium-ion batteries, as a highly efficient energy storage system, play an important role in electric vehicles, portable electronic devices and renewable energy storage. From the perspective of battery material chemistry, the energy density of lithium-ion batteries depends largely on the performance of the positive electrode material. x Mn y Co (1-x-y) O2 has become a high energy density cathode material widely used in the current market. Among them, the ultra-high nickel ternary cathode material LiNi 0.9 Co 0.05 Mn 0.05 O2(NCM) has gradually taken a dominant position in the research field of ternary positive electrode materials due to its high specific capacity.
[0003] However, this high-nickel material still faces many challenges in practical application, which affects its stability and lifespan. First, when the NCM cathode material is exposed to air, the H + Will react with Li in the positive electrode material + Proton exchange occurs, resulting in the loss of active lithium and the destruction of local crystal structure. The loss of a large amount of active lithium will cause the battery capacity to drop rapidly. In addition, high-nickel positive electrode materials are prone to form impurity layers during storage, including residual lithium compounds, transition metal oxides, and adsorbed species. The residual lithium compounds are mainly Li2CO3, LiHCO3, and LiOH. These electrochemically inert lithium compounds will hinder the Li + The diffusion channel increases the energy barrier of the (de)lithiation reaction, thereby reducing the rate performance and cycle stability of the material. In addition, the residual lithium compounds are prone to defluorination reaction with PVDF, resulting in a decrease in slurry viscosity and even slurry gelation, which poses great difficulties for industrial production. In addition, during long-term electrochemical cycles, the highly active Ni 4+ It is easy to react with carbonate-based electrolytes, causing a series of negative effects, including the formation of residual alkali on the surface, material phase change, dissolution of transition metal ions, microcrack formation, and gas generation.
[0004] Long-chain fluorides (such as Chinese patent CN 117558895) or silicon-based materials (such as Chinese patent CN 112436110) are often used to improve the moisture sensitivity of high-nickel cathode materials due to their excellent hydrophobic properties, and are widely used in improving the air storage stability of ultra-high nickel cathode materials. However, most of these hydrophobic materials are electrochemically inert substances, and they fail to have the ion-conducting properties required for ideal coating materials at the same time, and it is difficult to cope with the multiple challenges faced by high-nickel cathode materials. Based on this, the present invention uses pentafluorophenylpropyltrimethoxysilane (PFPPS) with hydrophobic fluorine groups and hydrophilic methoxy groups as a surface modifier to construct a multifunctional self-assembled molecular layer on the surface of NCM cathode materials. This strategy achieves the multiple protective effects of removing residual lithium on the surface, in-situ generating a coating layer and a surface hydrophobic layer through a simple one-step self-assembly, significantly improving the air storage stability of NCM cathode materials, effectively inhibiting the dissolution of transition metal ions, improving lithium ion transmission, and enhancing structural stability. This invention provides a broader development prospect for the application of ultra-high nickel positive electrode materials, especially in improving their environmental tolerance and cycle performance, showing great potential. Summary of the invention
[0005] The object of the present invention is to provide a preparation method of a modified NCM positive electrode material and its application, so as to improve the air storage stability and electrochemical stability of the NCM positive electrode material.
[0006] The technical solution of the present invention is as follows: A method for preparing a modified NCM positive electrode material comprises the following steps:
[0007] (1) dispersing 0.01-0.06 g of pentafluorophenylpropyltrimethoxysilane in 15-25 mL of dimethyl carbonate according to a mass ratio to form a dispersion;
[0008] (2) adding 1-3 g of NCM positive electrode material to the dispersion prepared in step (1), ultrasonicating at 40 kHz ultrasonic frequency for 20-40 min, and stirring at 70-90° C. for 1.5-2.5 h to obtain an NCM material solution;
[0009] (3) The NCM material solution prepared in step (2) is separated by centrifugation to obtain a modified NCM material precipitate, which is dried under vacuum conditions at 105-115° C. for 10-14 h to obtain a modified NCM positive electrode material sample.
[0010] In the above step (1), 0.02-0.04 g of pentafluorophenylpropyltrimethoxysilane is dispersed in 20 mL of dimethyl carbonate according to a mass ratio to form a dispersion.
[0011] Specifically, in the aforementioned step (1), 0.03 g of pentafluorophenylpropyltrimethoxysilane is dispersed in 20 mL of dimethyl carbonate according to a mass ratio to form a dispersion.
[0012] In the above step (2), 1.5-2.5 g of NCM positive electrode material is added to the dispersion prepared in step (1), ultrasonicated at 40 kHz ultrasonic frequency for 25-35 min, and then stirred at 75-85° C. for 1.8-2.2 h to obtain an NCM material solution.
[0013] Specifically, in the aforementioned step (2), 2 g of NCM positive electrode material is added to the dispersion prepared in step (1), ultrasonicated at 40 kHz ultrasonic frequency for 30 min, and then stirred at 80° C. for 2 h to obtain an NCM material solution.
[0014] In the above step (3), the NCM material solution prepared in step (2) is separated by centrifugation to obtain a modified NCM material precipitate, which is then dried at 110° C. under vacuum conditions for 12 h to obtain a modified NCM positive electrode material sample.
[0015] A modified NCM positive electrode material prepared by the aforementioned method.
[0016] The use of the aforementioned modified NCM positive electrode material, wherein the modified NCM positive electrode material is used as a positive electrode active material for a lithium ion battery.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] 1. The present invention uses pentafluorophenylpropyltrimethoxysilane (PFPPS) having both hydrophobic fluorine groups and hydrophilic methoxy groups as a surface modifier to construct a multifunctional self-assembled molecular layer on the surface of the NCM cathode material. This strategy can efficiently remove residual lithium on the surface, form a protective layer in situ and establish a hydrophobic barrier through a simple one-step self-assembly process, thereby significantly improving the air storage stability and electrochemical performance of the ultra-high nickel cathode material.
[0019] 2. Specifically, in order to verify the air storage stability of the modified samples, NCM / PFPPS-1.5wt% and unmodified Pristine NCM were stored in an environment of 60%-70% humidity and 25°C. SEM results showed that the PFPPS modified layer evenly covered the NCM surface. After 7 days of exposure, Li2CO3 flocculent particles appeared on the surface of Pristine NCM, while there was no obvious change on the surface of NCM / PFPPS-1.5wt%. This shows that the air storage stability of NCM has been significantly improved after modification.
[0020] 3. The modified NCM positive electrode material shows higher electrochemical stability. Specifically, after 50 cycles of charge and discharge at a rate of 1C (1C = 200mAh / g), the capacity retention rate of the NCM / PFPPS-1.5wt% positive electrode material reached 98.8%, while the capacity retention rate of the uncoated Pristine NCM was only 85.3%; after being exposed to air for 7 days, the capacity and capacity retention rate of the modified sample were basically unaffected, while the capacity of the uncoated Pristin e NCM was only 69.7mAh / g.
[0021] 4. The preparation process of the present invention is simple and suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 : SEM images of Pristine NCM and NCM / PFPPS-1.5wt% samples before and after storage in air (a1: unexposed Pristine NCM; a2: unexposed NCM / PFPPS-1.5wt%; a3: Pristine NCM after storage in air for seven days; a4: NCM / PFPPS-1.5wt% after storage in air for seven days);
[0023] Figure 2 : Cycling curves of unexposed samples in the voltage range of 2.8-4.3 and at 1C rate;
[0024] Figure 3 : Cycling curves of the sample at 1C rate after exposure to air for 7 days. DETAILED DESCRIPTION
[0025] The present invention is further described below by way of examples. However, it should be understood that the examples are used to explain the embodiments of the present invention, and the protection scope of the present invention is not limited by the examples within the scope of the subject matter of the present invention.
[0026] Embodiment 1:
[0027] Preparation method of modified NCM positive electrode material:
[0028] (1) dispersing 0.03 g of pentafluorophenylpropyltrimethoxysilane in 20 mL of dimethyl carbonate according to a mass ratio to form a dispersion;
[0029] (2) adding 2 g of NCM positive electrode material to the dispersion prepared in step (1), ultrasonicating at 40 kHz for 30 min, and stirring at 80 ° C for 2 h to obtain an NCM material solution;
[0030] (3) The NCM material solution prepared in step (2) was separated by centrifugation to obtain a modified NCM material precipitate, which was dried under vacuum conditions at 110° C. for 12 h to obtain a modified NCM positive electrode material sample, recorded as NCM / PFPPS-1.5wt%.
[0031] Embodiment 2:
[0032] Preparation method of modified NCM positive electrode material:
[0033] (1) dispersing 0.02 g of pentafluorophenylpropyltrimethoxysilane in 20 mL of dimethyl carbonate according to a mass ratio to form a dispersion;
[0034] (2) adding 2 g of NCM positive electrode material to the dispersion prepared in step (1), ultrasonicating at 40 kHz for 30 min, and stirring at 80 ° C for 2 h to obtain an NCM material solution;
[0035] (3) The NCM material solution prepared in step (2) was separated by centrifugation to obtain a modified NCM material precipitate, which was dried under vacuum conditions at 110° C. for 12 h to obtain a modified NCM positive electrode material sample, recorded as NCM / PFPPS-1wt%.
[0036] Embodiment 3:
[0037] Preparation method of modified NCM positive electrode material:
[0038] (1) dispersing 0.04 g of pentafluorophenylpropyltrimethoxysilane in 20 mL of dimethyl carbonate according to a mass ratio to form a dispersion;
[0039] (2) adding 2 g of NCM positive electrode material to the dispersion prepared in step (1), ultrasonicating at 40 kHz for 30 min, and stirring at 80 ° C for 2 h to obtain an NCM material solution;
[0040] (3) The NCM material solution prepared in step (2) was separated by centrifugation to obtain a modified NCM material precipitate, which was dried under vacuum conditions at 110° C. for 12 h to obtain a modified NCM positive electrode material sample, recorded as NCM / PFPPS-2wt%.
[0041] Embodiment 4:
[0042] Preparation of CR2032 half-cell: The active materials acetylene black and polyvinylidene fluoride (PVDF) were uniformly mixed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 to prepare electrode slurry. The mixed slurry was evenly applied on aluminum foil and dried in a vacuum oven at 110°C overnight. The NCM / PFPPS-1.5wt% electrode material was punched into a circular electrode with a diameter of 12 mm. The CR2032 half-cell was assembled in an argon glove box (H2O≤0.01ppm, O2≤0.01ppm). Metal lithium was used as the counter electrode, Celgard2400 was used as the diaphragm, and 1M LiPF6 was dissolved in a mixture of ethyl carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (EC:DMC:DEC=1:1:1) as the electrolyte.
[0043] Embodiment 5:
[0044] Preparation of CR2032 half-cell: The active materials acetylene black and polyvinylidene fluoride (PVDF) were uniformly mixed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 to prepare electrode slurry. The mixed slurry was evenly applied on aluminum foil and dried in a vacuum oven at 110°C overnight. The NCM / PFPPS-1wt% electrode material was punched into a circular electrode with a diameter of 12 mm. The CR2032 half-cell was assembled in an argon glove box (H2O≤0.01ppm, O2≤0.01ppm). Metal lithium was used as the counter electrode, Celgard2400 was used as the diaphragm, and 1M LiPF6 was dissolved in a mixture of ethyl carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (EC:DMC:DEC=1:1:1) as the electrolyte.
[0045] Embodiment 6:
[0046] Preparation of CR2032 half-cell: The active materials acetylene black and polyvinylidene fluoride (PVDF) were uniformly mixed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 to prepare electrode slurry. The mixed slurry was evenly applied on aluminum foil and dried in a vacuum oven at 110°C overnight. The NCM / PFPPS-2wt% electrode material was punched into a circular electrode with a diameter of 12 mm. The CR2032 half-cell was assembled in an argon glove box (H2O≤0.01ppm, O2≤0.01ppm). Metal lithium was used as the counter electrode, Celgard2400 was used as the diaphragm, and 1M LiPF6 was dissolved in a mixture of ethyl carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (EC:DMC:DEC=1:1:1) as the electrolyte.
[0047] Comparative Example 1:
[0048] The untreated NCM cathode material is recorded as Pristine NCM.
[0049] Comparative Example 2:
[0050] Preparation of CR2032 half-cell: The active materials acetylene black and polyvinylidene fluoride (PVDF) were uniformly mixed in N-methylpyrrolidone (NMP) at a mass ratio of 8:1:1 to prepare electrode slurry. The mixed slurry was evenly applied on aluminum foil and dried in a vacuum oven at 110°C overnight. Pristine NCM electrode material was punched into a circular electrode with a diameter of 12 mm. CR2032 half-cell was assembled in an argon glove box (H2O≤0.01ppm, O2≤0.01ppm). Metal lithium was used as the counter electrode, Celgard2400 was used as the diaphragm, and 1M LiPF6 was dissolved in a mixture of ethyl carbonate (EC), dimethyl carbonate (DMC) and diethyl carbonate (DEC) (EC:DMC:DEC=1:1:1) as the electrolyte.
[0051] Experimental Example 1: SEM Characterization Analysis
[0052] In order to reveal the changes in the physical and chemical properties of NCM with PFPPS added after exposure to air, the Pristine NCM of Comparative Example 1 and the NCM / PFPPS-1.5wt% sample prepared in Example 1 were placed in a watch glass and exposed to an environment with an ambient humidity of 60%-70% and a temperature of about 25°C for 0 days and 7 days respectively. The microstructure of the samples was characterized and analyzed using a scanning electron microscope (SEM). PFPPS did not change the particle size and morphology of the NCM, and both showed blocky single crystal particles of about 1 to 5 μm.
[0053] See Figure 1 , the multifunctional molecular layer modified by PFPPS is evenly covered on the surface of NCM. After 7 days of exposure, some flocculent particles are gradually seen covering the surface of Pristine NCM. These flocculent particles are mainly Li2CO3 impurities formed by exposure to air, while almost no flocculent particles are observed on the surface of NCM / PFPPS-1.5wt%. This phenomenon is due to the reaction of water in the air with the surface of NCM, specifically manifested as Li2CO3 impurities that migrate from the bulk phase to the surface. + Continue to diffuse outward, and the H + Then it migrates inwards, and Li + / H +The ion exchange reaction eventually generates byproducts such as LiOH, Li2CO3 and LiHCO3. The specific reaction equations are shown in the following equations (1) to (3). The polyfluorinated chain PFPPS has strong hydrophobicity, so the self-assembly of PFPPS on the NCM surface can effectively inhibit the undesirable ion exchange reaction at the cathode material-air interface and improve the storage stability of the material in the air.
[0054] Li + +H2O→H + +LiOH (1)
[0055] LiOH+CO2→LiHCO3 (2)
[0056] LiOH+LiHCO3→H2O+Li2CO3 (3)
[0057] Example 2: Electrochemical Measurements
[0058] The half-cells prepared in Examples 4-6 and the half-cells prepared in Comparative Example 2 were tested at different rates (1C = 200 mAh g -1 )、2.8~4.3V(vs.Li / Li + ) constant current charge and discharge test under voltage, the capacity retention rate after 50 cycles is shown in Table 1. Figure 2 .
[0059] Table 1: Half-battery capacity retention test results
[0060] Half-cell Electrode Materials Capacity retention rate Example 4 NCM / PFPPS-1.5wt% 98.8% Example 5 NCM / PFPPS-1wt% 85.7% Example 6 NCM / PFPPS-2wt% 91.2% Comparative Example 2 Pristine NCM 85.3%
[0061] like Figure 2 As shown in the figure, the optimal coating amount of PFPPS is 1.5wt%, and the corresponding capacity retention rate is 98.8%, showing excellent cycle stability. This is mainly due to the dense and uniform protective layer formed by PFPPS on the surface of NCM material, which effectively blocks the corrosion of electrolyte to positive electrode material on the one hand, and on the other hand, through the electron-withdrawing effect of F group, Ni 2+ It is firmly anchored on the NCM surface, significantly inhibiting the dissolution of transition metal ions, thereby enhancing the reversibility of the phase change of the NCM positive electrode, thereby greatly improving its overall electrochemical performance.
[0062] Experimental Example 3: Electrochemical Measurement
[0063] The Pristine NCM and NCM / PFPPS-1.5wt% samples were then exposed to air for 7 days and subjected to long cycle tests under the same conditions. The electrochemical measurement results are shown in Figure 3As shown in the figure, NCM / PFPPS-1.5wt% still exhibits excellent cycle stability and capacity advantages after exposure to air, which is close to that of the unexposed sample. In contrast, the capacity retention rate of the uncoated Pristine NCM is only 69.7mAh / g, and the material surface is reconstructed, which seriously affects its electrochemical performance.
[0064] Summarize
[0065] The present invention develops a multifunctional self-assembled protective layer strategy based on pentafluorophenylpropyltrimethoxysilane (PFPPS), which significantly improves the ultra-high nickel positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 Air storage stability and electrochemical cycling performance of O2(NCM). By introducing a PFPPS molecular layer on the surface of NCM, a dense hydrophobic protective layer is formed, which can effectively block moisture and CO2 in the air and prevent them from corroding NCM, thereby avoiding material degradation caused by environmental factors. The coating not only slows down the deactivation of the material during storage and processing, but also significantly enhances the electrochemical stability of NCM in long-term cycles. Specifically, the PFPPS self-assembled protective layer increases the overall valence state of Ni ions on the surface of NCM through the strong electron-withdrawing effect of the fluorine group, thereby effectively inhibiting the dissolution of transition metal ions. At the same time, the LiF protective layer near the PFPPS layer promotes the transmission of lithium ions, reduces the impedance increase during the electrochemical cycle, and enhances the reversibility of the phase change, thereby further improving the electrochemical performance. The experimental results show that the PFPPS-modified NCM still exhibits excellent electrochemical stability even after air exposure, and its capacity retention rate is significantly higher than that of the unmodified sample. This modification strategy shows significant advantages in improving the moisture sensitivity and electrochemical stability of ultra-high nickel cathode materials, showing a wide range of practical application potential.
Claims
1. A method for preparing a modified NCM positive electrode material, characterized in that : Includes the following steps: (1) dispersing 0.01-0.06 g of pentafluorophenylpropyltrimethoxysilane in 15-25 mL of dimethyl carbonate according to a mass ratio to form a dispersion; (2) adding 1-3 g of NCM positive electrode material to the dispersion prepared in step (1), ultrasonicating at 40 kHz ultrasonic frequency for 20-40 min, and stirring at 70-90° C. for 1.5-2.5 h to obtain an NCM material solution; (3) The NCM material solution prepared in step (2) is separated by centrifugation to obtain a modified NCM material precipitate, which is dried under vacuum conditions at 105-115° C. for 10-14 h to obtain a modified NCM positive electrode material sample.
2. The method for preparing the modified NCM positive electrode material according to claim 1, characterized in that: In the step (1), 0.02-0.04 g of pentafluorophenylpropyltrimethoxysilane is dispersed in 20 mL of dimethyl carbonate according to a mass ratio to form a dispersion.
3. The method for preparing the modified NCM positive electrode material according to claim 2, characterized in that: In the step (1), 0.03 g of pentafluorophenylpropyltrimethoxysilane is dispersed in 20 mL of dimethyl carbonate according to a mass ratio to form a dispersion.
4. The method for preparing the modified NCM positive electrode material according to claim 1, characterized in that: In the step (2), 1.5-2.5 g of NCM positive electrode material is added to the dispersion prepared in step (1), ultrasonicated at 40 kHz ultrasonic frequency for 25-35 min, and then stirred at 75-85° C. for 1.8-2.2 h to obtain an NCM material solution.
5. The method for preparing the modified NCM positive electrode material according to claim 4, characterized in that: In the step (2), 2 g of NCM positive electrode material is added to the dispersion prepared in the step (1), ultrasonicated at a frequency of 40 kHz for 30 min, and then stirred at 80° C. for 2 h to obtain an NCM material solution.
6. The method for preparing the modified NCM positive electrode material according to claim 1, characterized in that: In the step (3), the NCM material solution prepared in the step (2) is separated by centrifugation to obtain a modified NCM material precipitate, which is then dried at 110° C. under vacuum conditions for 12 h to obtain a modified NCM positive electrode material sample.
7. A modified NCM positive electrode material obtained by the method according to any one of claims 1 to 6.
8. The use of the modified NCM positive electrode material according to claim 7, characterized in that: The modified NCM positive electrode material is used as a positive electrode active material for lithium ion batteries.
Citation Information
Patent Citations
Organosiloxane resin composition and laminate comprising same
CN102449072A
Fluorosilane-coated composite positive electrode material as well as preparation method and application thereof
CN112421039A
Positive electrode active material for nonaqueous secondary battery
US20150349336A1